Din broders vogter - Schwarz, Finn (Rambam. Tidsskrift for jødisk kultur og forskning, 2017)
Your Brother's Guardian In this article, one of the founders of the Danish Jewish security system explains the background for establishing the system in the beginning of the 1980s. The author follows the Jewish security system from the start up to the present, evaluating the different threats the last 30-35 years have presented. In the end of the article, the author comments on the terror attack in February 2015, which resulted in the killing of one of the guards.